√50 + √72 - √8
√(25*2) + √(36*2) - √(4*2)
√25√2 + √36√2 - √4√2
5√2 + 6√2 - 2√2
9√2
2006-11-25 07:43:19
·
answer #1
·
answered by Jim Burnell 6
·
1⤊
0⤋
â50 = 5â2 (50 = 25*2)
â72 = 6â2 (72 = 36*2)
â8 = 2â2 (8 = 4*2)
â50 + â72 - â8 = (5+6-2) * â2 = 9â2 = (â81)*(â2)
= â(2*81) = â162
2006-11-25 15:46:34
·
answer #2
·
answered by Morosoph 2
·
1⤊
0⤋
you would simplify first - 50 becomes 5 root 2, 72 becomes 6 root 2 and 8 bcomes 2 root 2. then because they are all the same inside the root you can add/subrtact the first number. So 5 + 6 - 2 = 9. therefore the answer is 9 root 2
2006-11-25 15:45:27
·
answer #3
·
answered by bballgirl90 2
·
0⤊
0⤋
How did you get that?
Let's see what perfect squares are in those numbers:
50 =2*5^2,
72=12*6 = 2*6^2
8 = 2*2^2
so
2^(1/2)*5 + 2^(1/2)*6 - 2^(1/2)*2
there's a common factor
2^(1/2)[5+6-2] = 2^(1/2)*9 =
9*2^(1/2) is the best form.
2006-11-25 15:45:37
·
answer #4
·
answered by modulo_function 7
·
0⤊
0⤋
i got 114 in radical form, i dont know how to do the radical on my keyboard but im sue you unsersand what i mean
2006-11-25 15:42:09
·
answer #5
·
answered by ash 2
·
0⤊
2⤋
get a TI -89 Calculator and figure it out dude..
2006-11-25 15:46:00
·
answer #6
·
answered by the_ron 2
·
0⤊
1⤋
the answer is just sqr(50)+sqr(72)-sqr(8) because you can't add radicals
2006-11-25 15:42:15
·
answer #7
·
answered by 7
·
0⤊
2⤋